0852 Characterizing Sleep Disorders in Veterans who are Diagnostically Eligible for Cardiac Rehabilitation. (12th April 2019) - Tighe, Caitlan; Kelly, Monique; Walker, Jon; Hanusa, Barbara; Allsup, Kelly; Forman, Daniel; Buysse, Daniel; Bramoweth, Adam
Abstract: Introduction: The prevalence of sleep disorders is high in individuals with cardiovascular disease. It may be further heightened in individuals who have recently experienced a cardiac event, undergone a cardiac procedure, or have a chronic heart condition (i.e., individuals eligible for cardiac rehabilitation [CR]). Factors related to the cardiac event or disease-process (e.g., hospitalization, physiology, medications) as well as psychosocial factors (e.g., mood) may precipitate or exacerbate sleep disorders in this group. The objective of this analysis was to estimate the prevalence of sleep disorders in Veterans eligible for CR. Methods: Analysis was conducted with Veterans Affairs (VA) Electronic Health Records data. The total sample included Veterans who utilized VA VISN 4 services from FY2011-FY2017. The sample of interest was Veterans who were diagnostically eligible for CR, indicated by receipt of International Classification of Diseases (ICD) or Current Procedural Terminology codes corresponding with CR diagnostic enrollment criteria. Sleep disorders were identified using ICD codes. Data on prescription medications for insomnia was also collected. Results: Of 482, 164 Veterans who utilized VA VISN 4 services from FY2011-FY2017, 68, 485 were diagnostically eligible for CR. Of Veterans eligible for CR, 27.4% had at least one sleep disorder, and 5.2% had more than one. Breathing-Related Sleep Disorders were the most commonly diagnosed sleep disorders (20.2%), followed by Insomnia Disorders (9.6%), Sleep-Related Movement Disorders (1.5%), and Parasomnias (1.4%). Approximately 20.4% of Veterans eligible for CR were prescribed an insomnia medication. Conclusion: The prevalence of sleep disorders, indicated by a diagnosis or prescription medication, was high in this sample of Veterans eligible for CR. These findings provide preliminary support for the need to routinely assess and monitor sleep in this population. The assessment of sleep and implementation of interventions that promote sleep health could enrich existing CR goals and enhance Veterans' revitalization and long-term well-being. Support (If Any): VA Pittsburgh Healthcare System, VISN 4 Mental Illness Research, Education and Clinical Center Pilot Funds; Department of Veterans Affairs Office of Academic Affiliations, Advanced Fellowship Program in Mental Illness Research and Treatment.